Perceptions of the characteristics of the Alberta Nutrition Guidelines for Children and Youth by child care providers may influence early adoption of nutrition guidelines in child care centres - Nikolopoulos, Hara (Matern Child Nutr, 2012)
In 2008, the Alberta government released the Alberta Nutrition Guidelines for Children and Youth (ANGCY) as a resource for child care facilities to translate nutrition recommendations into practical food choices. Using a multiple case study method, early adoption of the guidelines was examined in two child care centres in Alberta, Canada. Key constructs from the Diffusion of Innovations framework were used to develop an interview protocol based on the perceived characteristics of the guidelines (relative advantage, compatibility, complexity, trialability and observability) by child care providers. Analysis of the ANGCY was conducted by a trained qualitative researcher and validated by an external qualitative researcher. This entailed reviewing guideline content, layout, organisation, presentation, format, comprehensiveness and dissemination to understand whether characteristics of the guidelines affect the adoption process. Data were collected through direct observation, key informant interviews and documentation of field notes. Qualitative data were analysed using content analysis. Overall, the guidelines were perceived positively by child care providers. Child care providers found the guidelines to have a high relative advantage, be compatible with current practice, have a low level of complexity, easy to try and easy to observe changes. It is valuable to understand how child care providers perceive characteristics of guidelines as this is the first step in identifying the needs of child care providers with respect to early adoption and identifying potential educational strategies important for dissemination.